2008
DOI: 10.1111/j.1537-2995.2008.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Very low hepatitis C antibody levels predict false‐positive results and avoid supplemental testing

Abstract: The high prediction rate of false-positive anti-HCV results using very low levels by the Ortho VITROS anti-HCV assay safely avoids the need for supplemental testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 25 publications
6
53
1
3
Order By: Relevance
“…However, lower and/or upper cut-off values for the S/Co ratio vary between studies, even for the same assay [6,7,[9][10][11]. This study provides the first results for the Elecsys Anti-HCV II assay, but further studies are necessary to confirm these findings.…”
Section: S/co Ratiosupporting
confidence: 59%
See 1 more Smart Citation
“…However, lower and/or upper cut-off values for the S/Co ratio vary between studies, even for the same assay [6,7,[9][10][11]. This study provides the first results for the Elecsys Anti-HCV II assay, but further studies are necessary to confirm these findings.…”
Section: S/co Ratiosupporting
confidence: 59%
“…Results of the RecomLine HCV strip immunoassay performed in 276 samples with an S/Co ratio ≥ 1. A number of previous studies have reported the threshold S/Co ratios for a variety of anti-HCV IgG assays [6,7,[9][10][11], and the CDC has published a list of S/Co ratios predictive of a true positive result ≥ 95% of the time for six different immunoassays [1,2]. The Elecsys Anti-HCV II immunoassay was reported to have superior performance compared to several other commercially available assays [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, we analyzed HCV S/Co ratios by using ROC curves to develop an improved algorithm for HCV testing in our veteran population. Applying ROC curve analyses as previously described by Contreras et al (6 ), we determined that the optimal high S/Co ratio cutoff for confirmation of HCV exposure by RIBA testing is 20.0 (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Son zamanlarda bu konuda yapılan ça-lışmalarda, anti-HCV S/Co değerinin viremiyi kestirmede önemli olduğu ve yüksek S/Co değerlerinin HVR-RNA ile daha uyumlu olduğu belirtilmekte ve HCV enfeksiyonunu tanısında kullanılabilecek en iyi S/Co değerleri önerilmektedir. [5][6][7][8] Biz de bu çalışmada kullandığımız anti-HCV mikropartikül EIA testinin viremiyi öngörmedeki performansını, ve bu test için duyarlılık ve özgül-lük yönünden en uygun S/Co değerini tespit etmek istedik. Veri analizinde, HCV enfeksiyonu tanısında viremiyi belirleyen HCV-RNA testi altın standart olarak kabul edilerek, anti-HCV testinin viremiyi öngörmedeki performansı ve özgüllük, duyarlılık ve prediktif değerleri SPSS v15.0 istatistik programında hesaplanarak belirlendi.…”
unclassified